2020
DOI: 10.1515/jpem-2020-0549
|View full text |Cite
|
Sign up to set email alerts
|

Graves’ disease in a five-month-old boy with an unusual treatment course

Abstract: ObjectivesGraves’ disease (GD) is rare in children under age five years. Antithyroid drugs are typically first-line therapy but carry the risks of agranulocytosis and liver dysfunction.Case presentationA male infant with multiple congenital anomalies, left ventricular hypertrophy, and neurologic dysfunction developed GD at five months of life. The presence of chronic hepatitis complicated medical management. Potassium iodide was effective temporarily, but urgent thyroidectomy was required at nine months of age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Azova et al identified a heterozygous de novo duplication of the ATAD3 gene cluster in a male infant with multiple congenital anomalies, left ventricular hypertrophy, and neurological dysfunction [51]. The infant developed endogenous Graves' disease at five months of age.…”
Section: Copy Number Variantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Azova et al identified a heterozygous de novo duplication of the ATAD3 gene cluster in a male infant with multiple congenital anomalies, left ventricular hypertrophy, and neurological dysfunction [51]. The infant developed endogenous Graves' disease at five months of age.…”
Section: Copy Number Variantsmentioning
confidence: 99%
“…The infant developed endogenous Graves' disease at five months of age. Graves' disease is an autoimmune disease that can lead to hyperthyroidism characterized by excessive production of thyroid hormone and is uncommon in children under five years old [51,55]. Azova et al suspected a possible mitochondrial dysfunction that may potentially account for a novel pathophysiology for early-onset Graves' disease [51,56,57].…”
Section: Copy Number Variantsmentioning
confidence: 99%